ВПЛИВ ФАКТОРУ РОСТУ ФІБРОБЛАСТІВ 19 НА СТАН ВУГЛЕВОДНОГО ОБМІНУ У ХВОРИХ НА ЦУКРОВИЙ ДІАБЕТ 2 ТИПУ З СУПУТНЬОЮ БІЛІАРНОЮ ПАТОЛОГІЄЮ (World Science, 2019)
This article analyzes the changes of fibroblast growth factor 19 (FRF-19) in serum content and presence of the connections between this marker and carbohydrate metabolism in patients with diabetes mellitus type 2 and chronic cholecystitis, as well as in patients with isolated chronic cholecystitis. 34 patients with type 2 diabetes mellitus and concomitant chronic cholecystitis and 31 patients with isolated chronic cholecystitis were examined in the gastroenterologic and endocrinological departments of «Regional Clinical Hospital» (Kharkiv, Ukraine). Determination of FRF-19 level was carried out by enzyme immunoassay. In patients with combined course of type 2 diabetes mellitus and concomitant chronic cholecystitis, there is a significant decrease in serum FRF-19 concentration, an increase in glycemia, insulinemia and insulin resistance, determined by the HOMA index, compared with patients with isolated chronic cholecystitis, in whom high concentrations of FRF-19 were accompanied by no disturbance of carbohydrate metabolism.